Kaidah Fiqih sebagai Solusi dalam Problematika Bioetika Kontemporer - Rahmadani, Citra Oktavia; Caningtyas, Sofya Carren Desi; Rahman, Fatimah Zahra; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2025)
The rapid development of science and technology, particularly in the fields of health and biotechnology, has given rise to complex bioethical issues such as genetic engineering, in vitro fertilization, organ transplantation, cloning, and euthanasia. These issues have sparked not only scientific and medical debates but also raised moral, social, and religious concerns. In this context, fiqh principles serve as a vital instrument within Islamic law, offering a flexible and contextual framework to address contemporary bioethical dilemmas that are not explicitly regulated in the scriptural texts (nash). Foundational maxims such as al-dharurat tubih al-mahzurat (necessity permits the prohibited), dar’ul mafasid muqaddam ‘ala jalbil mashalih (preventing harm takes precedence over obtaining benefit), and al-‘adah muhakkamah (custom is a legal consideration) provide rational foundations for establishing rulings on modern ethical issues. This approach not only ensures the alignment of biomedical practices with Sharia values but also affirms the relevance of fiqh principles as a basis for ethical and legal judgment. Therefore, the integration of fiqh maxims into bioethical discourse offers both normative and practical solutions, safeguarding public welfare amid ongoing scientific advancement.